Modern weapons and military equipment for issue 3-2020 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2020)
Modernization of the Moscow anti-missile shield; Turkey chooses Ukrainian active protection system Zaslon; New Swedish submarine; Firefly: Israeli "wandering" ammunition (or kamikaze drone); The MZ-204 Highlander mortar prototype is ready; Operation Desert Shield and dron Baryaktar TB2